Tree species distribution in natural forest and the factors affecting its diversity and structure in Menit Goldia Woreda, Western Omo Zone, Southwestern Ethiopia - Mehari Hadush; Biniam Tesfaye; Biniam Assefa; Alemitu Worku (CV. Literasi Indonesia, 2026)
This research evaluated tree species distribution and determinants influencing diversity and structural composition within natural forests of Menit-Goldia Woreda. Data collection occurred in three Kebelles using both primary and secondary sources. Primary data were acquired through field observations and systematically sampled forest plots. A total of 35 forest plots (300, 400, and 500 m²) were established along transect lines spaced 50-100 meters apart. Tree density, height, and Diameter at Breast Height measurements characterized vegetative structure. Regeneration status was assessed in five 1m × 1m subplots, categorizing trees as saplings or seedlings. Interviews with 39 participants identified factors contributing to forest degradation using structured questionnaires during key informant interviews and focus group discussions. Data analysis utilized SPSS and Microsoft Excel with descriptive statistics and Pearson correlation analysis. The survey identified 16 tree species across 11 families, with Fabaceae being the most predominant, followed by Moraceae and Combretaceae. The Shannon-Wiener diversity index (H') and evenness value (J) were 2.5 and 0.92, respectively. Millettia ferruginea and Comberut mole had the highest frequency (20.7% of total basal area). Comberut mole exhibited the highest Importance Value Index (IVI), followed by Ficus vasta and Cordia Africana, while Ficus sur had the lowest. Seedlings, saplings, and adult trees comprised 20.8%, 16.8%, and 62.4% of the population, respectively, indicating fair regeneration. Significant negative correlations existed between forest decline and population growth (-0.95), agricultural expansion (-0.91), resettlement (-0.79), and charcoal production (-0.64). Conservation efforts should include raising local awareness, exploring alternative livelihood options, and promoting afforestation initiatives.